The Gender Roles in Chinese Textbooks: A Multimodal Discourse Analysis - Liu, Dan (Journal of Theory and Practice in Linguistics, 2024)
How to integrate the gender roles into education has become a hot topic in the field of educational research. Textbooks play an important role to educate the gender equality, especially in the lower grades of primary school. Therefore, this paper uses visual grammar which is proposed by Kress and van Leeuwen to analyze the illustrations in the Chinese textbooks edited by the Chinese Ministry of Education for the first grade of primary school. Observing the illustrations in the first-grade Chinese Textbooks, this paper finds that the frequency of female and male roles appeared in the illustrations are respectively 105/115 and 57/64; the frequency of material process and verbal process are 42/24 and 39/19; the frequency of female and male roles appeared in the verbal process are 14/17 and 9/13; the frequency of demand and offer are 9/57 and 8/53; the frequency of female and male roles appeared in the demand are 2/7 and 1/7; the frequency of social distance are 0/11/59 and 1/19/42; the frequency of female and male roles appeared in the medium shot are 11/6 and 14/13; the illustrations in the first-grade Chinese textbooks represent in oblique and eye-level angle; the female roles always wear pink or red dresses and male roles always wear in blue and the female and male role in the selected pictures always strongly framed. In conclusion, gender stereotypes and gender biases still exist. But the compilers of the textbooks intend to attach importance to both of female and male. This paper analyzes the causes: the acceptance of the developed thinking and the laws to protect female roles in society; and put forward some feasible suggestions to the education of gender roles in the textbooks.